The hemochromatosis protein HFE 20 years later: An emerging role in antigen presentation and in the immune system - Reuben, Alexandre (Immun Inflamm Dis, 2017)
INTRODUCTION: Since its discovery, the hemochromatosis protein HFE has been primarily defined by its role in iron metabolism and homeostasis, and its involvement in the genetic disease termed hereditary hemochromatosis (HH). While HH patients are typically afflicted by dysregulated iron levels, many are also affected by several immune defects and increased incidence of autoimmune diseases that have thereby implicated HFE in the immune response. Growing evidence has supported an immunological role for HFE with recent studies describing HFE specifically as it relates to MHC I antigen presentation. METHODS/RESULTS: Here, we present a comprehensive overview of the relationship between iron metabolism, HFE, and the immune system to better understand the origin and cause of immune defects in HH patients. We further describe the role of HFE in MHC I antigen presentation and its potential to impair autoimmune responses in homeostatic conditions, a mechanism which may be exploited by tumors to evade immune surveillance. CONCLUSION: Overall, this increased understanding of the role of HFE in the immune response sets the stage for better treatment and management of HH and other iron‐related diseases, as well as of the immune defects related to this condition.